If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = (x + -4) * 2 Reorder the terms: 0 = (-4 + x) * 2 Reorder the terms for easier multiplication: 0 = 2(-4 + x) 0 = (-4 * 2 + x * 2) 0 = (-8 + 2x) Solving 0 = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 0 + -2x = -8 + 2x + -2x Remove the zero: -2x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 -2x = -8 + 0 -2x = -8 Divide each side by '-2'. x = 4 Simplifying x = 4
| =(9x+6)(9x-6) | | =(7x+1)(7x-1) | | X=14+-6x | | =(8a+5b)(8a-5b) | | =(3a+11)(3a-11) | | 6.5/3x+5 | | -9x-7y=3 | | (6z^10)(-5z^6)(z^2)= | | 4x^2+16x^2=225 | | -6(x-4)=36 | | -400.00x+4000.00=0.00 | | (5x^2+3y^2-4)-(2x^2+3y^2-2)= | | X^2/3-3x^4/3=0 | | 6x-2/3=6 | | 2x/5+2=22 | | (3x-5)/2 | | (2x+1)/(4x-1) | | 4-x=-20 | | 25.00s=500.00 | | X^3-2x^2-4x=-8 | | ax-ay-by-bx= | | 225-y^10= | | Y-175=25(x-7) | | (3x-6)/(8x-9)=0 | | 4^5/2 | | Y-375=25(x-7) | | 4x+6=10+6x | | L=2L/2w | | 4/5*2/6= | | n=b/d-a+1 | | (2x+4)/(2x^2-8) | | 2x+4/x-7 |